Women and religion in the first Christian centuries - Sawyer, Deborah F., 1956- (Religion in the first Christian centuries, 1996)
"Too often the religious traditions of antiquity are studied in isolation, without any real consideration of how they interacted. What made someone with a free choice become an adherent of one faith rather than another? Why might a former pagan choose to become a 'God-fearer' and attend synagogue services? Why might a Jew become a Christian? How did the mysteries of Mithras differ from the worship of the Unconquered Sun, or the status of the Virgin Mary from that of Isis, and how many gods could an ancient worshipper have? These questions are hard to answer without a synoptic view of what the different religions offered."--Jacket